Perception of Rural Dwellers on Girl - Child Education in Saki East Local Government Area of Oyo State - Adebisi, G. L; Oyebode, L. A.; Balogun, O. T (The Nigerian Journal of Rural Extension and Development, 2023)
This study examined perception of rural dwellers on girl-child education in Saki East local government area of Oyo state. A multi-stage sampling procedure was used to select the respondents, resulting in a total number of 120 household heads used for this study. Primary data on the perception of rural dwellers on girl-child education was collected using interview schedule and were analyzed using descriptive and inferential statistics. Results reveal that majority (75.8%) of the respondents were male, within 41-50 years of age and were aware of girl-child education through the use of the radio (81.7%). Further results show that majority (85.0%) of the respondents had favorable perception of girl-child education. Chi-square analysis of the result shows that there was a significant relationship between the level of education of the respondents (?2 = 4.379, p = 0.002), awareness on girl-child education (?2 = 5.441, p = 0.020) and their perception of girl-child education. Further results of correlation analysis revealed that there existed a correlation between income (r = -0.592, p= 0.000), the constraints facing rural dwellers on girls’ education (r = -0.465, p = 0.000) and their perception on girl-child education. Based on these findings, the study recommended that adult literacy should be encouraged and the cost of acquiring formal education should be subsidized.